Tunneling for the Eastlink Project, Melbourne, Australia - Harry R. Asche; Edmund G. Taylor; P. Scott Smith; Peter Campi; Ian P. Callow (Society for Mining, Metallurgy & Exploration, 2007)
The US$1,850 million EastLink project is a 39km tollway and includes twin 3-lane,1.5km long, undrained driven tunnels. The hard rock tunnels are being built to avoid passing the motorway through the Mullum Mullum Valley and so to help preserve the unique flora and fauna in the area. This paper describes several of the key issues in the tunnel design and construction, including: the integration of the temporary support design with the Contractor’s tunnel excavation and support procedures, including sharing of responsibility between the Designer and Contractor for support type selection and the production of a project specific rock mass classification system to enable more objective determination of ground conditions. detailed hydrogeological assessments during the design and construction phases to allow confirmation of design loads for the tunnel lining design and the various suite of waterproofing tools in order to meet the project inflow requirements. development of a pre-cast invert solution to the main tunnel secondary lining to enable faster lining construction and to minimize risks to the tunnel membrane associated with fixing reinforcement and construction traffic.